Literature review: analisis efektivitas pendekatan pendidikan karakter dalam membangun nilai-nilai moral di lingkungan sekolah - salsabila, salma nehaya (Maliki Interdisciplinary Journal, 2026)
Character education in schools has a very important role in forming moral values ​​in students. This research aims to analyze the effectiveness of various character education approaches in building moral values ​​in the school environment. This research uses a Systematic Literature Review with data taken from Google Scholar and Publish or Perish over the last 10 years. Character education that is integrated into the curriculum and accompanied by the example of Giri and the support of a conducive school environment can form a generation with noble and responsible character. Existing literature demonstrates various approaches to improving morals and character in students. Existing literature demonstrates that an integrated character education approach across various subjects and other approaches is highly effective in addressing the problem of character decline in teachers.